The investigation of copper (cu), iron (fe), total iron binding capacity (tibc) and zn levels of blood serum of the ewes in izmir region - Ali Muhtar Tiftik; Selma (Çınar) Doğanay (Eurasian Journal of Veterinary Sciences)
In this research designed for determining Cu,Fe,Tolal iron binding capacity (TIBC) and Zn levels of blood serum of the healthy ewes grazed in the meadows in Izmir Region, a total of 250 units of blood-samples, being from a; least 10 ewes in each herd, were collected from different 15 herds belonging to various villages ot some different counties of İzmir (Karşıyaka, Seferihisar, Torbalı, Kemalpaşa. Urla) After eliminated sera that shows haemolyses, copper (Cu), Iron (Fe), Total Iron Binding Capacity (TIBC) and Zinc levels were analyzed by atomic absorption spectrophotometer in 210 sera. In the assessments respect to serum Cu, Fe, TIBC and Zn leves, considerable diversities-being at p< 0,01 levels- from the statistical point ot view were observed between the average values of the counties and herds Although there were considerable differences from county to county, the average values of these counties and herds that indicated the lowest values in respects o1 iron and zinc contents, were found to be either similar to or just over the normal values. Therefore, it can be stated that the meadows of the counties in questions are rich enough in the elements investigated, and so, there is no need for adding those elements in to ewes rations. In the result of the assessment considering only the copper content, the average serum copper-level of the ewes (rom Torbalı County of Izmir was found to be remarkably lower, with a rate of p<0.01, than those from other counties. This level is actually lower than the limits of normal values.The average values o! only one among the herds in Torbalı and 54.54% rate of the entire ewes when considered the individual values, have been found to be lower than the deficiency limit. Under the light of all these findings, taking apart the fact that no soil and plant analyses were executed during the research, we can claim thai the meadow soil and plant levels in this county lack in copper and the rations of those animals grazing at meadows are required to be reinforced with copper content.